2000
DOI: 10.1042/bj3510289
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful relationships: the regulation of the Ras/Raf/MEK/ERK pathway by protein interactions

Abstract: The Ras\Raf\MEK (mitogen-activated protein kinase\ERK kinase)\ERK (extracellular-signal-regulated kinase) pathway is at the heart of signalling networks that govern proliferation, differentiation and cell survival. Although the basic regulatory steps have been elucidated, many features of this pathway are only beginning to emerge. This review focuses on the role of protein-protein interactions in the regulation of this pathway, INTRODUCTIONThe mitogen-activated protein kinase (MAPK) pathway is one of the primo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,050 publications
(139 citation statements)
references
References 178 publications
1
118
0
10
Order By: Relevance
“…Is Ras dimerization necessary? Data support Ras dimerization and higher oligomerization increasing signalling output and promoting Raf's activation [1,2,68,69]. This is backed by structural considerations.…”
Section: Figure 7 the Two Types Of Ras Dimers And The Outcome For Rafmentioning
confidence: 77%
“…Is Ras dimerization necessary? Data support Ras dimerization and higher oligomerization increasing signalling output and promoting Raf's activation [1,2,68,69]. This is backed by structural considerations.…”
Section: Figure 7 the Two Types Of Ras Dimers And The Outcome For Rafmentioning
confidence: 77%
“…Mitogen-activated protein kinase (MAPK) pathways exist in all eukaryotes and control a wide range of cellular processes, such as proliferation, differentiation, and survival (Kolch, 2000). We previously demonstrated that H9N2 AIV activates interferon (IFN) regulatory factor (IRF)-7.…”
Section: Resultsmentioning
confidence: 99%
“…p38 protein has been related to neuronal stress and the control of cell death and survival (44), while the role of ERK1/2 on this balance is controversial. This protein has been usually linked to a pro-survival function (45); however, several studies demonstrated a role of ERK1/2 on oxidative stress-induced apoptosis (33, 4648). This is in agreement with our results, where an increase of pERK1/2 was observed after SIN-1 treatment.…”
Section: Discussionmentioning
confidence: 99%